Hypertension and vascular endothelial growth factors - Luizon, Marcelo Rizzatti [UNESP]; Sandrim, Valeria Cristina [UNESP] (Springer Nature, 2015)
The members of vascular endothelial growth factors (VEGF) are the principal regulators of angiogenesis and vascular biology. The specific growth factor of the endothelial cells is VEGF, which produces nitric oxide (NO) from endothelial cells causing vasodilation. VEGF-A, the best characterized and the most biologically active isoform, is critical for endothelial cell survival, inhibits apoptosis, increases vascular permeability, and stimulates vasodilation. VEGF-A is also a positive regulator of tumor growth and metastases. VEGF inhibitors are effective antiangiogenic agents used to treat cancer. However, hypertension is the most reported adverse effect of angiogenesis inhibitors interfering with VEGF signaling. Since VEGF stimulates vasodilation and NO, which plays a critical role in blood pressure control, VEGF may affect blood pressure regulation. Interestingly, a specific combination of polymorphisms in the VEGF gene (haplotype) is present more frequently in normotensive than in hypertensive subjects, and the same haplotype is found in subjects with higher plasma nitrite/nitrate levels (circulating markers of NO formation). This supports the hypothesis that impaired NO bioavailability contributes to clinical hypertension. Regarding hypertensive disorders of pregnancy, NO formation is inversely related to the antiangiogenic factors soluble VEGF receptor-1 (sFlt-1) and soluble endoglin levels in patients with preeclampsia, characterized by hypertension and proteinuria. Antihypertensive therapy may produce their effects by enhancing NO bioavailability, thus counteracting the impaired NO formation reported in these hypertensive disorders of pregnancy.
Keywords: Endoglin; Endothelial cells; Hypertension; Nitric oxide; Polymorphisms; Preeclampsia; VEGF